Hanna KOMOROWSKA (Ed.) Issues in Promoting Multilingualism. Teaching – Learning – Assessment. Warsaw: Foundation for the Development of the Education System (FRSE), 2011. 360 pp. ISBN 978-83-62634-19-4 - Cybulska, Katarzyna (Linguarum Arena, 2018)
.